Patient safety culture from nursing staff perception - Larico Peralta, Yeny (2021)
Objective: To determine the patient’s safety culture from the perception of nursing staff in a surgical center service. Material and methods: Quantitative, nonexperimental, descriptive, cross-sectional study. The study was conducted in 15 nursing graduates and 12 nursing technicians who work in the Surgical Center of the Hipólito Unanue Hospital in Tacna, Peru. A questionnaire with informed consent was applied. The statistical package SPSS was used to process the information. Results: The best characteristic in nurses was contact with the patient (92 %). In terms of dimensions, for most indicators the results were neutral (mid-point). Specifically in the dimension of culture of communication, in the culture of security, safety at the level of service and safety culture at the level of the hospital. Conclusion: The best feature presented by the nurses of the Surgical Center Service is the approach to the patient with 92.6 % and in terms of indicators of the dimensions of the patient safety culture is positive organizational learning by 63 %.